2020
DOI: 10.1021/acs.jproteome.0c00383
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Drug Repurposing for SARS-CoV-2 Main Proteinase and Spike Proteins

Abstract: The pandemic caused by SARS-CoV-2 is currently representing a major health and economic threat to humanity. So far, no specific treatment to this viral infection has been developed and the emergency still requires an efficient intervention. In this work, we used virtual screening to facilitate drug repurposing against SARS-CoV-2, targeting viral main proteinase and spike protein with 3000 existing drugs. We used a protocol based on a docking step followed by a short molecular dynamic simulation and rescoring b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 76 publications
5
59
0
Order By: Relevance
“…The same study also reported potential binding of indinavir to RdRp [ 56 ]. Several other studies also reported indinavir as a potential drug to target M pro /3CL pro [ 46 , 47 , 55 , 57 , 58 ]. Indu et al also reported good bioavailability of indinavir [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The same study also reported potential binding of indinavir to RdRp [ 56 ]. Several other studies also reported indinavir as a potential drug to target M pro /3CL pro [ 46 , 47 , 55 , 57 , 58 ]. Indu et al also reported good bioavailability of indinavir [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Except indinavir, the others (Pibrentasvir, baloxavir marboxil, doravirine, maraviroc, and nelfinavir) have been shown to cause rare cases of hepatotoxicity in toxicological studies [ 44 ]. Maffucci and Contini predicted binding of indinavir to ACE2 at the site that overlaps with the binding of SARS-CoV-2 spike protein [ 55 ]. In a virtual screening of 65 FDA approved small molecule antiviral drugs against the main protease (Mpro, also called 3CL pro ) and the RNA-dependent RNA polymerase (RdRp), indinavir and pibrentasvir were predicted to bind Mpro of SARS-CoV-2 [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several computational drug screening methods based on molecular docking, deep learning or Molecular Dynamics (MD) simulations have been applied in drug repositioning studies for COVID-19 [9,[11][12][13][14]. However, most of these normally rely on a single technique or lacks experimental validation.…”
Section: Introductionmentioning
confidence: 99%